Demonstration of a memory calibration method in water isotope measurement by laser spectroscopy. (21st February 2020) - Qu, Dongmei; Tian, Lide; Zhao, Huabiao; Yao, Ping; Xu, Baiqing; Cui, Jiangpeng
Abstract : Rationale: Measuring δ 18 O and δ 2 H values in water using wavelength‐scanned cavity ring down spectroscopy (WS‐CRDS) requires multiple injections of up to six (and sometimes eight or more) of one sample to remove the memory effect, which decreases the sample throughput and increases the consumables cost. Thus, improved methods for removing the memory effect are required. Methods: We calculated the memory coefficients by sequential WS‐CRDS measurement of two lab standard waters with isotopic differences, and used them to establish calibration equations. We then used these equations to correct the measured δ 18 O and δ 2 H values by removing the memory effect, instead of using multiple injections in the routine daily measurements. Results: By using this method, the number of injections per sample was reduced to one. The reproducibility (one standard deviation) of the δ 18 O and δ 2 H values obtained for quality control sample was less than 0.05‰ and 0.5‰ for an annual average, respectively. Conclusions: By measuring the memory coefficients and establishing the calibration equations, a highly effective method was developed for determining the δ 18 O and δ 2 H values of water, which could significantly improve sample throughput for liquid water dual isotope measurement without sacrificing the precision.